Tools of employee motivation in HOYA Electronic Malaysia Sdn Bhd. / Fadhlina Ahmad - Ahmad, Fadhlina (2014)
The aim of this survey is to identify tools of employee motivation and to recognize the level of employees’ motivation at HOYA Electronic Malaysia Sdn Bhd. (HOEM). With increasing demand of electronic product, HOEM needs to compete with other electronics companies to produce high quality of product for their customers. Employees are the most important element to produce product in the company. Some motivations are needed by employees to perform their task. This research will help to identify the tools of employee motivation that directly influenced employee performance in their job. Therefore, the study has been conducted at HOEM, Kulim branch. This study was conducted with a different demographic background of the respondent. The sample size comprises of 100 employees from HOEM. However, the researcher managed to recollect only 92 questionnaires out of 100. Respondent was asked to rate tools of employee motivation such as rewards and working environment and also rate their motivation level in doing their job. Questionnaires were composed in English language and Malay Language. Several data-analysis tools have been employed to dissect the data, such as a pilot test, demographic analysis, reliability analysis, descriptive analysis, correlation coefficient analysis and speculation. In conclusion, rewards and working environment were found to be significantly linked to employee motivation.